The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1029/2004ja010483
|View full text |Cite
|
Sign up to set email alerts
|

Energy deposition by Alfvén waves into the dayside auroral oval: Cluster and FAST observations

Abstract: [1] We report in situ observations from the Cluster and FAST spacecraft showing the deposition of energy into the auroral ionosphere from broadband ULF waves in the cusp and low-latitude boundary layer. A comparison of the wave Poynting flux with particle energy and flux at both satellites indicates that energy transfer from the broadband waves to the plasma occurs through field-aligned electron acceleration, transverse ion acceleration, and Joule heating. These processes are shown to result in precipitating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 128 publications
11
110
0
Order By: Relevance
“…The most likely source of the upgoing short duration electron beams inside the electron edge is a wave-particle interaction process. For example, it has been suggested that electrons could be trapped in the parallel electric fields associated with kinetic Alfvén waves and propagate with these waves (Chaston et al, 2005). A parallel electric field existing below the spacecraft and accelerating electrons is also a possible explanation (e.g., Paschmann et al, 2003).…”
Section: Discussion Of the Plasma Population Inside The Electron Edgementioning
confidence: 99%
“…The most likely source of the upgoing short duration electron beams inside the electron edge is a wave-particle interaction process. For example, it has been suggested that electrons could be trapped in the parallel electric fields associated with kinetic Alfvén waves and propagate with these waves (Chaston et al, 2005). A parallel electric field existing below the spacecraft and accelerating electrons is also a possible explanation (e.g., Paschmann et al, 2003).…”
Section: Discussion Of the Plasma Population Inside The Electron Edgementioning
confidence: 99%
“…The conclusion from that paper was that particle fluxes seen by Cluster in the exterior cusp were enough to heat the F layer, while the Poynting flux was more than enough to account for the Joule heating in the E ionospheric layer. Also, Chaston et al (2005) studied a conjunction between Cluster and FAST satellite, and a conclusion was, after a comparison of the Poynting and particle fluxes, that the energy deposition to the dayside auroral oval was due to field-aligned electron acceleration, transverse ion-acceleration, and Joule heating.…”
Section: T žIvković Et Al: Energy Deposition Through the Cuspmentioning
confidence: 99%
“…The utility of WT in space physics problems has been demonstrated by a growing number of authors [e.g., Muret and Omidi, 1995;Lui and Najmi, 1997;Gedalin et al, 1998;Lundstedt et al, 2005]. Recently, WT have been applied to the study of ULF waves either from space [Chaston et al, 2005] or from the ground [Waters, 2000]. However, there has not been so far a systematic study of the advantages and/or disadvantages of the WT over the usual FT in the determination of FLRs.…”
Section: Introductionmentioning
confidence: 99%